Wildland Urban Interface: Varied Definitions - L. Annie Hermansen-Baez; Jennifer A. Seitz; Martha C. Monroe (EDIS)
FOR225, a 4-page illustrated fact sheet by L. Annie Hermansen-Baez, Jennifer Seitz, and Martha C. Monroe, describes several common definitions of the wildland-urban interface (WUI) to assist natural resource professionals with new challenges and opportunities in the WUI. Includes references. Published by the UF Department of Wildlife Conservation and Ecology, July 2009.